Ultrasound at labour triage in eastern Uganda: A mixed methods study of patient perceptions of care and providers' implementation experience. - Nathan Isabirye (Public Library of Science (PLoS), 2021)
In settings where antenatal ultrasound is not offered routinely, ultrasound use when a woman first presents to the maternity ward for labour (i.e., triage) may be beneficial. This study investigated patients' perceptions of care and providers' experience with ultrasound implementation during labour triage at a district referral hospital (DH) and three primary health centers (HC) in eastern Uganda. This was a mixed methods study comprising questionnaires administered to women and key informant interviews among midwives pre- and post-ultrasound introduction. Bivariate analyses were conducted using chi-square tests. Qualitative themes were categorized as (1) workflow integration; (2) impact on clinical processes; (3) patient response to ultrasound; and (4) implementation barriers. A total of 731 and 815 women completed questionnaires from the HCs and DH, respectively. At the HC-level, triage quality of care, satisfaction and recommendation ratings increased with implementation of ultrasound. In contrast, satisfaction and recommendation ratings did not differ upon ultrasound introduction at the DH, whereas perceived triage quality of care increased. Most participants noted a perceived improvement in midwives' experience and knowledge upon introduction of ultrasound. Women who underwent a scan also reported diverse feelings, such as fear or worry about their delivery, fear of harm due to the ultrasound, or relief after knowing the baby's condition. For the midwives' perspective (n = 14), respondents noted that ultrasound led to more accurate diagnoses (e.g., fetal position, heart rate, multiple gestation) and improved decision-making. However, they noted health system barriers to ultrasound implementation, such as increased workload, not enough ultrasound-trained providers, and irregular electricity. While triage ultrasound in this context was seen as beneficial to mothers and useful in providers' clinical assessments, further investigation around provider-patient communication, system-level challenges, and fears or misconceptions among women are needed.